Impact of Comprehensive, Minimally Invasive, Multimodal Aesthetic Treatment on Satisfaction With Facial Appearance: The HARMONY Study. (13th December 2017) - Weinkle, Susan H; Werschler, W Philip; Teller, Craig F; Sykes, Jonathan M; Shamban, Ava; Rivkin, Alexander; Narurkar, Vic A; Kaminer, Michael S; Dayan, Steven; Cohen, Joel L; Gallagher, Conor J
Abstract: Background: Individuals seeking aesthetic treatment have concerns regarding multiple facial areas. Objectives: Assess the aesthetic impact and satisfaction achieved with a multimodal approach to aesthetic treatment using a combination of minimally invasive treatments. Methods: Prospective, multicenter, rater-blinded, 4-month HARMONY study evaluated patient satisfaction and aesthetic impact of a combination of fillers (VYC-20L, HYC-24L, and HYC-24L+), onabotulinumtoxinA, and bimatoprost. Males and females aged 35 to 65 years received on-label, staged treatment with fillers, as needed per investigator assessment, on day 1, with touch ups allowed on day 14. Bimatoprost was self-administered once daily for 17 weeks. OnabotulinumtoxinA was injected into glabellar lines, crow's feet lines, or both at month 3. Primary effectiveness measure was mean change from baseline on the FACE-Q 10-item Satisfaction with Facial Appearance Overall Scale. Results: Of 100 patients treated, 93 underwent at least the 4-month posttreatment assessment and were assessed for efficacy. The FACE-Q Satisfaction with Facial Appearance Overall Scale total score increased from baseline (41.2) to month 4 (72.9; P < 0.00001; effect size, 2.7). Improvement following multimodal treatment was observed on FACE-Q individual items. Self-perceived age decreased from 0.2 years older than actual age at baseline to 4.6 years younger at month 4. Nearly all patients (99%) rated themselves as improved or much improved on the Global Aesthetic Improvement Scale. Investigator assessments also demonstrated improvement. Mild to moderate adverse events occurred in 42 patients. Conclusions: Minimally invasive, multimodal treatment resulted in improvements in FACE-Q scores and perceived age, indicating a high degree of patient satisfaction and a younger facial appearance. Level of Evidence: 4: